Les ors surréalistes de la monnaie gauloise - Raphaël Neuville (Les Cahiers de Framespa)
After reviewing shortly the first tracks of the interest of the surrealistic movement for the gallic arts, we will linger on the rediscovery of gallic currencies in the fifties. For far too long, they have been retroceded to the rank of clumsy copies of greco-latin models, but the gallic coins were born again thanks to L’art gaulois dans les médailles, published in 1954. Behind André Malraux, Lancelot Lengyel lead an analysis on photographic enlargments of these coins. The surrealistic group was fascinated by the incredible plastic qualities they revealed. As a rupture with tradition, a new Antiquity is offered to sights. But this reinterpretation is not reduced to a numismatic erudition. We will analyse how André Breton bridges the gap between gallic art and contemporary creation. The exhibition Pérennité de l’art gaulois, in 1955, is the chance to answer a topical question by suggesting the surpassing of the quarrel between abstraction and figuration.